A Persons-Centered Approach for Prevention of COVID-19 Disease and Its Impacts in Persons With Disabilities - Senjam, Suraj Singh (Frontiers in Public Health, 2021)
The World Health Organization (WHO) considers COVID-19 a great threat to humanity and declared the COVID-19 outbreak a pandemic on March 11, 2020. To limit the transmission, governments announced lock down in their respective nations and recommended control measures, including behavior change. Persons with disabilities (PwDs) are among the population that may have a higher risk of getting infected and may suffer serious illnesses due to COVID-19. Additionally, the lockdown poses immense challenges and tremendous impacts to PwDs in terms of receiving their daily support. To mitigate these challenges, impacts and reduce the risk of infection, it is important to design strategies that can improve the overall outcome on PwDs. Therefore, the study intends to provide a uniform strategy or guideline using the person-centered approach principles that perhaps most feasible and implementable in circumventing those challenges faced by PwDs during the emergency lockdown with two case studies as examples. This pandemic also provides an opportunity for health reforms toward inclusiveness for an emergency lockdown in the future.